Research on coreference resolution technology of entity in information security - Han ZHANG; Yongjin HU; Yuanbo GUO; Jicheng CHEN (Tongxin xuebao)
To solve the problem of coreference resolution in information security,a hybrid method was proposed.Based on the BiLSTM-attention-CRF model,the domain-dictionary matching mechanism was introduced and combined with the attention mechanism at the document level.As a new dictionary-based attention mechanism,the word features were calculated to solve the problem of weak recognition ability of rare entities and entities with long length when extracting candidates from text.And by summarizing the features of the domain texts,the candidates were coreferenced by rules and machine learning according to the part of speech to improve the accuracy.Through the experiments on security data set,the superiority of the method is proved from the aspects of coreference resolution and extraction of candidates from text .